2020
DOI: 10.1038/s41598-020-66889-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Vitamin D Levels as a Predictor of Transient Hypocalcemia and Hypoparathyroidism After Parathyroidectomy

Abstract: Hypocalcemia is a common problem after parathyroidectomy and/or thyroidectomy. The complication may be transient or permanent. Most cases occur as a result of removal of the parathyroid glands or damage to the glands during neck surgery. The purpose of this study was to evaluate the effect of preoperative vitamin D deficiency in predicting transient hypocalcemia and hypoparathyroidism after parathyroidectomy.Retrospective evaluation was made of 180 patients with primary hyperparathyroidism in respect of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…Soares et al did, however, show that hypocalcemia is dependent on postoperative levels of PTH [ 13 ]. Unsal et al, on the other hand, in their study, showed that there was a significant drop in postoperative calcium levels following parathyroidectomy in patients with vitamin D deficiency and vitamin D insufficiency [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soares et al did, however, show that hypocalcemia is dependent on postoperative levels of PTH [ 13 ]. Unsal et al, on the other hand, in their study, showed that there was a significant drop in postoperative calcium levels following parathyroidectomy in patients with vitamin D deficiency and vitamin D insufficiency [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…e relationship of vitamin D and postoperative hypoparathyroidism or hypocalcemia has been evaluated in a number of studies, but the results are controversial. Several studies reported that low preoperative 25OHD was associated with postoperative hypoparathyroidism or hypocalcemia [11,[21][22][23]. Bove et al [11] analyzed clinical and lab data of 177 patients who underwent total thyroidectomy and found preoperative vitamin D deficiency (<25 ng/mL) was an independent risk factor in the development of hypocalcemia [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies were able to demonstrate the association between low vitamin D status and increased bone turnover [ 65 ] as well as decreased BMD (FN, distal radius, whole body) [ 66 ]. Vitamin D insufficiency was also identified as an independent risk factor for post-operative hypocalcemia [ 67 , 68 , 69 ] and hungry bone syndrome [ 70 ]. Concerns regarding the effects of vitamin D repletion on further elevating serum calcium in PHPT have not been validated.…”
Section: General Measures Calcium and Vitamin Dmentioning
confidence: 99%